Comparison of local effects of ginger oil with oral ginger on associated symptoms of primary dysmenorrhea: randomized clinical trial - Pantea Shirooye; Maryam Hamzeloo-Moghadam; Fataneh Hashem-Dabaghian; Roshanak Mokaberinejad (Mashhad University of Medical Sciences, 2017)
Introduction: Primary dysmenorrhea along with associated symptoms is followed by many consequences. According to Iranian Traditional Medicine point of view and the studies, oral and topical ginger are effective on primary dysmenorrhea. So this study was performed with aim to evaluate the effect of oral ginger capsule and topical ginger oil which are prepared by Maceration method on the associated symptoms of dysmenorrhea and comparing their effects. Methods: This single-blind randomized clinical trial was performed on 70 students with moderate and severe dysmenorrhea who were resident in dormitory of Tehran Shahid Beheshti University of Medical Sciences in 2016-2017. The associated symptoms of dysmenorrhea in these students were assessed with verbal multidimensional scoring system in first cycle. Then, the patients were randomized into two groups of oral and topical and they received drugs two days before the start of menstruation until first three days of menstruation over next three cycles. The oral group received one ginger capsule every 6 hours and the topical group applied 5 drops of ginger oil below the abdomen every 6 hours. The associated symptoms of dysmenorrhea were assessed and compared in each cycle based on verbal multidimensional scoring system. Data were analyzed by SPSS software (version 17) and Mann-Whitney and Wilcoxon tests. P< 0.05 was considered significant. Results: Fatigue, bloat, headache, backache and leg cramps decreased in both groups compared to before the intervention (p<0.05). Nausea, vomiting and diarrhea decreased in oral group, and mood's changes and leg pain decreased in topical group (p<0.05) after the intervention. Side effects were observed only in oral group (60%). Conclusion: Both forms of ginger reduced general and neurological symptoms of dysmenorrhea; the oral form decreased more gastrointestinal symptoms of dysmenorrhea and topical form decreased more musculoskeletal symptoms of dysmenorrhea. In addition, since topical form was better tolerated by patients, so it seems that topical ginger oil is a better choice for reducing the general and neurological symptoms of dysmenorrhea.